Integrasi Artificial Intelligence dalam Pendidikan: Peluang, Tantangan, dan Etika Pembelajaran Modern - Bintang Mufidia Rizqi; Elsya Novitasari Anggraini; Muhammad Nadhif Mirzaq (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The rapid development of Artificial Intelligence (AI) has significantly influenced the field of education, particularly in transforming learning processes towards the use of digital technology. This study aims to discuss the integration of AI in education, covering basic concepts, opportunities, challenges, and the importance of character education alongside Pancasila values. The method used is a qualitative literature review by analyzing journals and scientific sources related to AI in education. The results indicate that AI can create a more effective, interactive, and flexible learning ecosystem through adaptive systems while supporting students' digital literacy. However, AI utilization also poses serious challenges, such as an increased risk of plagiarism, technological dependence, the digital divide, and reduced social interaction. Therefore, AI must be used wisely and responsibly. Integrating humanistic values, justice, and mutual cooperation is essential so that technology remains a supportive tool without replacing the teacher's strategic role in shaping students' character in the modern era.